THE INFLUENCE OF DPJP'S KNOWLEDGE, ATTITUDE AND PRACTICE ON THE COMPLETENESS OF INFORMED CONSENT AT HUSADA HOSPITAL - Prasetyo, Widodo Budi; Holipah, Holipah; Rahmah, Shofi Nur (Universitas Brawijaya, 2025)
Informed consent refers to a patient’s or their family’s approval of a medical procedure following a thorough explanation. It serves as a key indicator in hospital Minimum Service Standards, which aim for 100% completeness. In 2023, informed consent completeness at Hospital X reached 92.7%, failing to meet this target. One factor affecting completeness is the knowledge, attitude, and practice of Physicians in Charge of Services (DPJP). This quantitative study adopts a cross-sectional design with observational data collection. The study used saturated sampling, targeting Medical Staff Group (KSM) physicians with low informed consent completeness. Conducted from April to August 2024, it involved 67 physicians. Data were analyzed using logistic regression, with informed consent completeness as the dependent variable and knowledge, attitude, and practice as independent variables. Results show that knowledge, attitude, and practice influence informed consent completeness, both partially and simultaneously, but not significantly. Medical Records Unit data from 2023 indicate that the most frequent issue was missing physician signatures (78.8%). Questionnaire responses on physicians' practice indicate that 44.8% of respondents frequently delegated the task of completing informed consent forms to others, while 7.5% always did so.